2019
DOI: 10.1073/pnas.1904024116
|View full text |Cite
|
Sign up to set email alerts
|

The deaminase APOBEC3B triggers the death of cells lacking uracil DNA glycosylase

Abstract: Human cells express up to 9 active DNA cytosine deaminases with functions in adaptive and innate immunity. Many cancers manifest an APOBEC mutation signature and APOBEC3B (A3B) is likely the main enzyme responsible. Although significant numbers of APOBEC signature mutations accumulate in tumor genomes, the majority of APOBEC-catalyzed uracil lesions are probably counteracted in an error-free manner by the uracil base excision repair pathway. Here, we show that A3B-expressing cells can be selectively killed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 49 publications
1
58
2
Order By: Relevance
“…Our findings establish UNG2 as a novel and ubiquitous target for HDACi-mediated degradation. This may expand indications for HDACi towards synthetic lethality in APOBEC3B expressing tumors [10] and to increase efficiency of deaminase-mediated CRISPR-Cas9 gene therapy [11]. Our results may also aid efforts to purge HIV viruses from latent reservoirs and treatment of autoimmune disease.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Our findings establish UNG2 as a novel and ubiquitous target for HDACi-mediated degradation. This may expand indications for HDACi towards synthetic lethality in APOBEC3B expressing tumors [10] and to increase efficiency of deaminase-mediated CRISPR-Cas9 gene therapy [11]. Our results may also aid efforts to purge HIV viruses from latent reservoirs and treatment of autoimmune disease.…”
Section: Introductionmentioning
confidence: 75%
“…Finally, depletion of UNG was recently shown to induce synthetic lethality in APOBEC3B overexpressing cancers [10]. Many cancers overexpress APOBEC3B or harbor high kataegis mutational signatures conforming to deamination by the APOBEC/AID family of cytidine deaminases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APOBEC3B is a cytosine deaminase that converts cytosine to uracil and causes an accumulation of C to T signature mutations in cancer genomes. A knockout of UNG has been demonstrated to kill APOBEC3B expressing cells due to an accumulation of uracil lesions in a mechanism dependent on non-canonical mismatch repair (MMR) [ 20 ]. Consequently, there is a need to develop specific small molecule inhibitors to UNG.…”
Section: Inhibitors To the Ber Enzymesmentioning
confidence: 99%
“…Apolipoprotein B mRNA editing enzyme catalytic polypeptide-like 3B (APOBEC3B), an antiviral cytidine deaminase that induces DNA mutations, was considered as a medium for cancer development and therapeutic resistance [36]. Recent study have shown that the overexpression of APOBEC3B in tumor increased the resistance to chemotherapy and triggered anti-tumor T cells [37].…”
Section: Discussionmentioning
confidence: 99%